2009
DOI: 10.1093/nar/gkp112
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mouse transgenesis using Gateway-compatible ROSA26 locus targeting vectors and F1 hybrid ES cells

Abstract: The ability to rapidly and efficiently generate reliable Cre/loxP conditional transgenic mice would greatly complement global high-throughput gene targeting initiatives aimed at identifying gene function in the mouse. We report here the generation of Cre/loxP conditional ROSA26-targeted ES cells within 3–4 weeks by using Gateway® cloning to build the target vectors. The cDNA of the gene of interest can be expressed either directly by the ROSA26 promoter providing a moderate level of expression or by a CAGG pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 43 publications
(55 reference statements)
4
139
1
Order By: Relevance
“…Surviving clones were isolated and analyzed for homologous recombination by Southern blot using EcoRI and KpnI double-digested genomic DNA. Proper targeting was verified with 5′ and 3′ external probes [kindly provided by Christine Hartmann (Nyabi et al, 2009)]. Expression of the FLAG EnRCdx1-IRES-GFP bicistronic transcript after removal of the PGKpNeo stop cassette was verified by anti-FLAG western blotting analysis and GFP fluorescence following Cre transfection ( pMC-Cre) of one targeted ESC clone.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Surviving clones were isolated and analyzed for homologous recombination by Southern blot using EcoRI and KpnI double-digested genomic DNA. Proper targeting was verified with 5′ and 3′ external probes [kindly provided by Christine Hartmann (Nyabi et al, 2009)]. Expression of the FLAG EnRCdx1-IRES-GFP bicistronic transcript after removal of the PGKpNeo stop cassette was verified by anti-FLAG western blotting analysis and GFP fluorescence following Cre transfection ( pMC-Cre) of one targeted ESC clone.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…In theory, a reporter line driven by the ROSA26 locus or a CAG promoter is ubiquitously expressed, and recent work has demonstrated that the CAG promoter is eight to tenfold stronger than the ROSA26 promoter (Nyabi et al 2009;Chen et al 2011). xA more complex reporter line that is commonly used is Z/EG.…”
Section: Reporter Linesmentioning
confidence: 99%
“…45,46 Melanin content determination. Melanin was extracted with an alkaline solution as previously described.…”
mentioning
confidence: 99%